Pengaruh Infrastruktur, Investasi, dan Pertumbuhan Ekonomi terhadap Kesejahteraan Masyarakat melalui Kesempatan Kerja di Kabupaten Tapin - Yuaidi, Muhammad Najmi; Siregar, Syahrituah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study's purpose is to determine the effect of infrastructure, investment, and economic growth on employment opportunities in Tapin Regency, assess the impact of infrastructure, investment, and economic growth on people's welfare, choose the direct and indirect effects of infrastructure, investment, and the economic growth on the interest of the community through employment opportunities in Tapin Regency. This study uses the Path Analysis method's time series data from 2011 to 2020. Results of this study indicate that infrastructure and investment have no significant effect on employment opportunities, while economic growth substantially impacts employment opportunities. Furthermore, infrastructure and investment do not considerably affect people's welfare; economic growth considerably affects community welfare in Tapin Regency. Lastly, the influence of infrastructure and buying on the people's interest in Tapin Regency is a more dominant indirect influence. Economic growth on the welfare of the people in Tapin Regency is a more dominant direct effect.